Effect of Dolomite and NPK fertilizer on land Coal Mine Closure Of Plant Growth Rubber (Hevea brasiliensis) in Samarinda.: Pengaruh Pemberian Dolomit dan Pupuk NPK Pelangi pada Lahan Pasca Tambang Batubara Terhadap Pertumbuhan Tanaman Karet (Hevea brasiliensis) di Samarinda. - Arief Fathony; Rustam Baraq Noor; Mahdalena (Agrifarm : Jurnal Ilmu Pertanian, 2015)
Effect of Dolomite and NPK fertilizer on Coal Mine Closure Land for Plant Growth Rubber (Hevea brasiliensis). The purpose of this research know the effect of Dolomite lime and NPK fertilizer on Coal Mine Closure Land for medium rubber trees (Hevea brasiliensis) .Penelitian was conducted for 135 days, from July to November 2011, a post-mining land research Mining Authority PT. Bukit Baiduri Energy (BBE) Fruit Loa Village Sungai Samarinda.Rancangan City Kunjang used was a randomized block design (RAK) with factorial 4 x 4 are each repeated 5 times, the first factor which comprises four levels ie d0 (without calcification ), d1 (calcification of 500 g / hole), d2 (calcification of 750 g / hole) and d3 (liming 1000 g / hole). While the second factor which comprises the provision of NPK Pelangi 4 levels ie p0 (without fertilization), p1 (Provision of 40 g / tree), p2 (Provision of 50 g / tree) and P3 (Provision 60 g / tree). The results showed that administration of dolomite lime very significant effect on the parameters as height, stem diameter at the age of 45.90 and 135 days after planting, as well as the significant parameters of the number of umbrellas at the age of 135 days after planting. In the administration of NPK fertilizer treatment showed a significant influence on the parameters as height and diameter of the stem of the plant at the age of 90, 135 days after planting, while at the age of 45 days after planting NPK fertilizer significantly affected plant height and trunk diameter rubber plants on land post-mine coal. Interaction between giving Lime Dolomite and NPK rainbow showed significant effect on plant height and number of leaves crown / umbrellas at the age of 135 days after planting. Keywords: dolomite, NPK fertilizer and rubber plants